2011
DOI: 10.1037/a0021625
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two negatives: Differential memory modulation by threat-related facial expressions.

Abstract: Facial expressions serve as cues that encourage viewers to learn about their immediate environment. In studies assessing the influence of emotional cues on behavior, fearful and angry faces are often combined into one category, such as “threat-related,” because they share similar emotional valence and arousal properties. However, these expressions convey different information to the viewer. Fearful faces indicate the increased probability of a threat, whereas angry expressions embody a certain and direct threa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(108 citation statements)
references
References 64 publications
9
94
5
Order By: Relevance
“…Our results are consistent with previous studies that have shown enhanced retrieval performance for information paired with arousing stimuli during encoding and consolidation (Davis et al, 2011;Knight & Mather, 2009;Anderson, Wais, & Gabrieli, 2006;Nielson, Yee, & Erickson, 2005). The finding that retrieval speed was significantly faster for negative compared with positive locations supports the view that emotional enhancement effects are valence specific.…”
Section: Effect Of Different Emotional Event Schedulessupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are consistent with previous studies that have shown enhanced retrieval performance for information paired with arousing stimuli during encoding and consolidation (Davis et al, 2011;Knight & Mather, 2009;Anderson, Wais, & Gabrieli, 2006;Nielson, Yee, & Erickson, 2005). The finding that retrieval speed was significantly faster for negative compared with positive locations supports the view that emotional enhancement effects are valence specific.…”
Section: Effect Of Different Emotional Event Schedulessupporting
confidence: 83%
“…Valencespecific effects may reflect a natural bias of emotion regulation networks toward automatic processing of threatrelated information. Modulation of activity within the parahippocampal gyrus might be more important for negative stimulus events than for positive ones because the former are potentially threatening and thus have immediate survival value (Davis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for benefits has come from studies that have examined face identity memory or word memory in the context of neutral and emotional facial expressions (D'Argembeau & Van der Linden, 2011;Davis et al, 2011;Righi et al, 2012) or sentential contexts (Brierley, Medford, Shaw & David 2007;Guillet & Arndt, 2009;Phelps et al, 1997;Schmidt, 2012). Some facial emotion expressions were found to facilitate person or word memory relative to other expressions.…”
Section: Emotional Retrievalmentioning
confidence: 99%
“…However, the extant work is relatively silent on the question of whether emotional voices affect listeners beyond the immediate present. Moreover, while there is ample evidence for the long-term effects of other modes of emotional stimulation, including verbal content (Leclerc & Kensinger, 2011;Schmidt, 2012;Werner, Peres, Duschek & Schandry 2010), faces (D'Argembeau & Van der Linden, 2011;Davis et al, 2011;Righi et al, 2012), and images (Croucher, Calder, Ramponi, Barnard & Murphy 2011;Kaestner & Polich, 2011), as yet little evidence has emerged for long-term effects of the voice.…”
Section: Introductionmentioning
confidence: 99%
“…Intuitively though they might do. For example, fearful expressions are thought to warn of potential threat -a warning signal (Davis et al, 2011;Taylor & Whalen, 2014;Whalen, 1998) -therefore, responding cautiously by slowing down to avoid a mistake (trading speed for accuracy) is an intuitively plausible response to fearful expressions. For other emotional stimuli a speed-accuracy trade-off might lead to a different pattern.…”
Section: The Speed-accuracy Trade-offmentioning
confidence: 99%